Stigmasterol-based novel low molecular weight/mass organic gelators - Susteková, Jana; Drašar, Pavel; Saman, David; Wimmer, Zdeněk (Molecules (Basel, Switzerland), 2011)
Conjugates consisting of stigmasterol and L-phenylalanine, interconnected through short-chained dicarboxylic acyls by ester and amide bonds, respectively, were synthesized as potential low molecular weight/mass organic gelators (LMWGs/LMMGs). Their physico-chemical properties were subjected to investigation, especially their ability to form gels reversibly based on changes of the environmental conditions. Other self-assembly properties detectable by UV-VIS traces were measured in systems consisting of two miscible solvents (water/acetonitrile) with varying solvent ratios and using constant concentrations of the studied compounds. Partition and diffusion coefficients and solubility in water were calculated for the target conjugates. The conjugate 3a was the only compound from this series capable of forming a gel in 1-octanol. All three conjugates 3a-3c displayed supramolecular characteristics in the UV-VIS spectra.
Keywords: Stigmasterol; molekulová hmotnost; 1-Octanol; estery; Solvents; Amides; rozpouštědla; molekulární struktura; Molecular Structure; Gels; Esters; gely; organické látky; Organic Chemicals; Phenylalanine; stigmasterol; 1-oktanol; fenylalanin; amidy; Molecular Weight